2022
DOI: 10.2147/ccid.s372112
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Serum Exosomal Hsa-miR-487b-3p in Progressive Vitiligo Before and After Systemic Corticosteroid Treatment

Abstract: Background Vitiligo is an acquired skin depigmentation disease. It can be misdiagnosed at an early stage and tend to relapse. Serum markers are essential to monitoring the progression of vitiligo. Exosomal miRNAs act as the communication mediator between melanocytes and immune cells. Our study aimed to use serum exosomal miRNAs as a reference for evaluating vitiligo progression. Methods The miRNAs were extracted from the serum exosomes of ten progressive vitiligo patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Circulating exosomes from vitiligo patients, containing miR-21-5p, inhibited melanin content, tyrosinase activity, and melanogenesis-related protein expression in melanocytes via inhibiting SATB1 expression (47). Moreover, Luo et al reported that exosomal hsa-miR-487b-3p in serum was significantly lower in vitiligo patients and positively correlated with the area of lesions in progressive vitiligo patients (14). Keratinocytes are the main cell type in the epidermis and play an important role in maintaining melanocyte homeostasis.…”
Section: Exosomes In Vitiligo Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating exosomes from vitiligo patients, containing miR-21-5p, inhibited melanin content, tyrosinase activity, and melanogenesis-related protein expression in melanocytes via inhibiting SATB1 expression (47). Moreover, Luo et al reported that exosomal hsa-miR-487b-3p in serum was significantly lower in vitiligo patients and positively correlated with the area of lesions in progressive vitiligo patients (14). Keratinocytes are the main cell type in the epidermis and play an important role in maintaining melanocyte homeostasis.…”
Section: Exosomes In Vitiligo Pathogenesismentioning
confidence: 99%
“…The cargoes in circulating exosomes can be transferred to skin cells along with blood flow to promote the development of skin diseases 13 . For example, circulating exosomal miRNAs may serve as auxiliary indicative biomarkers for the diagnosis and progression of vitiligo 14 . In addition, exogenous exosomes, especially MSC-exos, possess huge potential in skin disease treatment and skin regeneration 5 .…”
Section: Introductionmentioning
confidence: 99%